Α‐Galacturonidase(s): A new class of Family 4 glycoside hydrolases with strict specificity and a unique CHEV active site motif. Issue 6 (14th February 2013) - Thompson, John; Pikis, Andreas; Rich, Jamie; Hall, Barry G.; Withers, Stephen G.
Abstract : The catalytic activity of the Family 4 glycosidase LplD protein, whose active site motif is CHEV, is unknown despite its crystal structure having been determined in 2008. Here we identify that activity as being an α‐galacturonidase whose natural substrate is probably α‐1, 4‐di‐galacturonate (GalUA2 ). Phylogenetic analysis shows that LplD belongs to a monophyletic clade of CHEV Family 4 enzymes, of which four other members are also shown to be galacturonidases. Family GH 4 enzymes catalyze the cleavage of the glycosidic bond, via a non‐canonical redox‐assisted mechanism that contrasts with Koshland's double‐displacement mechanism. Abstract : ► Family 4 glycosidases with a CHEV active site motif form a monophyletic clade. ► The crystal structure of one CHEV glycosidase (LplD) was determined in 2008. ► The catalytic activity of these enzymes has until now remained unknown. ► These enzymes are α‐galacturonidases. ► They employ a non‐canonical redox‐assisted catalytic mechanism.